Chemical kinetic analysis of detonability-enhancing strategies for ethylene–oxidizer mixtures. (November 2016) - St. George, Andrew; Driscoll, R.; Anand, V.; Gutmark, E.
Abstract: Four detailed chemical kinetic mechanisms are used in conjunction with an empirical detonation cell width model to numerically assess strategies to increase the detonation sensitivity of ethylene–oxidizer mixtures. Using this method, reasonable agreement is achieved with computed cell width and the available experimental data. Elevated initial pressures significantly reduce cell width for a wide range of equivalence ratios, yielding 80% reduction at stoichiometric conditions for a tenfold increase in pressure. Elevated initial temperatures have almost no effect on the cell width at stoichiometric conditions, but yield 80% reduction at lean conditions when the initial temperature is doubled. Reduced nitrogen dilution within the oxidizer dramatically reduces the cell width for the entire computed range of equivalence ratios. Introducing hydrogen as a fuel additive yields mild improvement to detonation sensitivity at stoichiometric conditions, but requires relatively high H2 concentrations and is ineffective when coupled with elevated initial pressures. Introduction of supplemental oxygen and increasing the initial reactant pressure appears to be the most effective approach to enhance detonability for ethylene–oxidizer mixtures. Highlights: Detailed chemical kinetic mechanisms are used to predict detonation cell width. Several methods are explored to boost detonability of ethylene–oxidizer mixtures. Elevated temperatures and hydrogen fuel substitution yield limited improvement. Elevated pressures and oxygen addition yield significant, widespread improvement.